2017
DOI: 10.1007/s10344-017-1113-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting hedgehog (Erinaceus europaeus) attraction to rural villages in arable landscapes

Abstract: Although residential areas are often unfavourable for wildlife, some species can take advantage of the available shelter and anthropogenic sources of food such as supplementary feeding. The European hedgehog (Erinaceus europaeus) is increasingly associated with gardens and villages and less so with arable farmland. Suggested drivers for this include the following: hedgehogs' attraction to higher food densities, including natural prey and anthropogenic sources, a greater range of day nest sites and warmer micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
84
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 75 publications
5
84
1
Order By: Relevance
“…The study of hedgehog ecology in urban areas is underrepresented in the literature, even though hedgehogs seem to prefer residential areas (Doncaster, Rondinini, & Johnson, ; Hubert, Julliard, Biagianti, & Poulle, ; Pettett, Moorhouse, Johnson, & Macdonald, ; van de Poel et al, ). This preference could be due to higher food densities affiliated with human occupation, including natural prey and anthropogenic sources, more suitable nest sites and a decreased risk of predation by badgers ( Meles meles ; Micol, Doncaster, & Mackinlay, ; Morris, ; Pettett et al, ; Young et al, ). In the UK, it is furthermore suggested that the hedgehog decline is currently more severe in the rural than urban areas (SoBH, ; Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The study of hedgehog ecology in urban areas is underrepresented in the literature, even though hedgehogs seem to prefer residential areas (Doncaster, Rondinini, & Johnson, ; Hubert, Julliard, Biagianti, & Poulle, ; Pettett, Moorhouse, Johnson, & Macdonald, ; van de Poel et al, ). This preference could be due to higher food densities affiliated with human occupation, including natural prey and anthropogenic sources, more suitable nest sites and a decreased risk of predation by badgers ( Meles meles ; Micol, Doncaster, & Mackinlay, ; Morris, ; Pettett et al, ; Young et al, ). In the UK, it is furthermore suggested that the hedgehog decline is currently more severe in the rural than urban areas (SoBH, ; Williams et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Immunocompromised people and pregnant women should take particular care when in contact with hedgehogs. Supplementary feeding of freeliving hedgehogs is an increasingly common practice; 14…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have commonly used fast curing epoxy for the attachment of devices to hedgehogs (Abu Baker et al, ; Bontadina, ; Braaker, ; Braaker et al, ; Braaker, Obrist, Bontadina, & Moretti, ; Esser, ; Pettett, Johnson, et al, ; Pettett, Moorhouse, et al, ; Reeve, ; Warwick et al, ). However, the hot glue we used was more suitable to fix the back pack on the hedgehog's spines as it was easy, cheap, and fast curing.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure is harmless because spines are made of keratin throughout and do not contain nerves or blood vessels. In contrast to previous studies of hedgehogs (Abu Baker, Reeve, Conkey, Macdonald, & Yamaguchi, ; Abu Baker et al, ; Braaker et al, ; Pettett, Johnson, et al, ; Pettett, Moorhouse, Johnson, & Macdonald, ; Reeve, ; Warwick et al, ), we used hot glue to attach the back plate because a mobile hot glue gun (neo1, Steinel Vertrieb GmbH, Herzebrock‐Clarholz, Germany) can be used very quickly and precisely and is cost effective. Hot glue sets within seconds and is therefore much faster and deliquesces much less than other commonly used and in this project previously tested glues and epoxies.…”
Section: Methodsmentioning
confidence: 99%